Odontogenic Keratocyst Imitating Lateral Periodontal Cyst: A Case Report - Thapa, Nabin; Acharya, Pujan; Shrestha, Ashish (Journal of Nepalese Society of Periodontology and Oral Implantology, 2023)
Collateral Odontogenic Keratocyst (OKC), a rare variant of OKC, is usually present in the mandibular premolar area and is often confused with lateral periodontal cysts due to common features. A 58-year-old male patient presented with a painless swelling in the mandibular left premolar area. The clinical and radiographical features were suggestive of a lateral periodontal cyst. Surgical enucleation followed by peripheral ostectomy was performed and the sample was sent for histopathological examination. The histopathological study demonstrated typical features of OKC. Owing to the high recurrence rate, the patient is kept on regular follow-up. During follow-ups, there were no clinical and radiographical signs of recurrences.